Unveiling the shades of partnerships for the energy transition and sustainable development: Connecting public-private partnerships and emerging hybrid schemes - Pinilla-De La Cruz Giovanna Andrea; Rabetino Rodrigo; Kantola Jussi (WILEY, 2022)
The transition to cleaner energy technologies and sustainable development requires the commitment and collaboration of the public and private sectors. Among such collaborations, public-private partnership (PPP) refers to the convergence and complementarity between public and private actors and represents an organizational arrangement for addressing strategic sustainability challenges such as reducing carbon emissions and plays a relevant role in transforming the sector after energy reforms. The rigidity of PPP schemes introduces certain limitations in adapting to the energy transition and sustainability needs. As a result, several hybrid schemes have emerged from PPPs, which are focal points in this paper. This article aims to contrast PPPs with emerging hybrid PPPs to facilitate their understanding. It contributes to the academic dialog on recognizing the relevance of emerging forms of collaboration in tackling contemporary issues. The review's primary outcome is a framework of PPPs and hybrid PPPs and the critical challenges for advancing the energy transition and sustainable development. The contributions from this study may help policymakers to design suitable tools for incorporating hybrid PPPs in climate change policies and institutional frameworks. The findings suggest developing mechanisms through which PPPs and hybrid PPPs foster cleaner technologies, thus improving energy efficiency and access and strengthening energy security strategies. Further work is needed to address key research issues related to (i) mechanisms for the institutional alignment of hybrid PPPs, (ii) assuring reciprocity and commitment, (iii) knowledge management, and (iv) capacity-building.